The severity level of malocclusion and orthodonthic treatment needs based on the index of orthodonthic treatment need (IOTN) on students aged 9-12 years old at candijati jember 1 state elementary school - Sukanto, Sukanto; Sulistiyani, Sulistiyani; Probosari , Niken; Herniyati, Herniyati; Wahyudi, Ilham; Prihatiningrum , Berlian; Setyorini , Dyah; Budi Rahardjo , Roedy (International Journal of Dental Research, 2024)
Malocclusion is a condition of dental occlusion that is not suitable from normal conditions that affect oral function and facial aesthetics and has now become a great concern in the health sector. Malocclusion occurs mostly in children aged 9-12 years which is the second phase of the mixed teeth period. The severity’s level of malocclusion and orthodontic treatment needs can be measured using the malocclusion index, one of which is the Index of Orthodontic Treatment Need (IOTN). Dental Health Component (DHC) is one component of IOTN that is effective in overcoming malocclusion and has good potential for orthodontic treatment because it assesses objectively by examining and measuring the circumstances of the teeth. The purpose of this study was to determine the severity of malocclusion and orthodontic treatment needs based on the Index of Orthodontic Treatment Need (IOTN) in students aged 9-12 years at SDN 01 Candijati Jember. Sampling was determined using the total sampling method on subjects encountered inclusion criteria; 96 samples were obtained. This study was conducted by measuring the study model of the patient's dental printing results based on DHC from IOTN and analyzed descriptively. The results of the study found the severity of malocclusion and the need for orthodontic treatment based on the Index of Orthodontic Treatment Need (IOTN) in students aged 9-12 years SDN 01 Candijati Jember is most commonly found in grade 2, namely mild malocclusion with little need for treatment. Then the severity’s level of malocclusion and the need for orthodontic treatment is greater in women than men and great-est in students aged 12 years.